"What is going on in the 'big tent'?" Current developments in (new) institutional theory and performance measurement and management research. Issue 6 (10th February 2022) - Polzer, Tobias
Abstract : Purpose: In a recent paper that was published in Journal of Public Budgeting, Accounting and Financial Management, Modell (2021) takes stock of the institutional research on performance measurement and management (PMM) in the public sector and proposes a number of avenues for further inquiry in the area. The aim of this comment is to contextualise some of his observations against the backdrop of current developments in (new) institutional theory. Design/methodology/approach: The recent scholarly debate about whether institutional theory needs any redirecting is the point of departure for this comment. Three of the themes from this debate are revisited and implications for research on PMM in the public sector are outlined. Findings: First, against the backdrop of an emerging plethora of organisational forms in the public sector, this comment focusses on the locus or "where" PMM can be analysed and how organisational forms affect PMM. The second point addresses the "what" of analysis, where it is argued that PMM instruments are embedded in an ecology of concepts and a relational perspective on diffusion is introduced. A third observation is related to methodological issues and discusses the "how": how best to study manifestations of PMM systems. Originality/value: The comment illustrates a number of implications of the current developments in (new) institutional theory for research on PMM. In so doing, the wider ambition is to stimulate an exchange between public-sector accounting and organisation studies.